The Effect of Company Image and Service Quality on Customer Loyalty with Customer Satisfaction as a Mediating Variable : (Case Study on CV. Sahabat Bumi in Merangin Regency, Jambi Province) - Pertiwi Mulyani; Reni Yuliviona; Rika Desiyanti; Zeshasina Rosha (Badan Penerbit STIEPARI Press, 2025)
This study is motivated by the fluctuating number of customers of CV. Sahabat Bumi, which operates in the palm oil trading sector in Merangin Regency, Jambi Province. The declining trend of customer loyalty highlights the need to examine the factors that influence it. The aim of this research is to analyze the effect of corporate image and service quality on customer loyalty with customer satisfaction as a mediating variable. This quantitative research involved 141 active customers who had made at least two transactions. Data were collected using a Likert-scale questionnaire and analyzed using structural equation modeling. The results show that corporate image has a positive effect on both customer loyalty and satisfaction, whereas service quality does not have a positive effect on either loyalty or satisfaction. Customer satisfaction is proven to mediate the relationship between corporate image and customer loyalty but does not mediate the relationship between service quality and loyalty. These findings indicate that customer loyalty at CV. Sahabat Bumi remains low, implying the need for the company to focus on improving service consistency, response speed, transparent communication, and corporate reputation to retain and enhance customer satisfaction and loyalty in the future. This research is expected to provide insights for management in formulating effective marketing strategies. Future research should consider adding other variables such as promotional mix or customer trust to produce more comprehensive results.